Antibiotic resistant bacteria from sediment of coastal water of Pahang, Malaysia - Ab Rahman, Nurhazlin; Khan Chowdhury, Ahmed Jalal; Zainal Abidin, Zaima Azira (2015)
The study was undertaken to determine the presence of antibiotic resistant bacteria in sediment of coastal water of Pahang, Malaysia. Coastal water of Pahang is known for fishing areas, recreation and water sports activities. However, the development of recreational areas, resorts and restaurants along the coastal area could be the sources to the flow of antibiotic contamination to the coastal water. A total of 125 bacteria were isolated from sediment samples of Tanjung Lumpur (A and B), Batu Hitam, Teluk Chempedak and Balok, Pahang by using dilution plate technique. The resistance of these bacteria to 10 different antibiotics was evaluated using disc diffusion method. The highly resistance isolates to antibiotics were identified by using API kit 20NE and API kit Staph. The greatest frequencies of resistance in bacteria were found in Polymyxin B and Streptomycin at Teluk Chempedak, Batu Hitam and Balok. The resistance in bacteria to Chloramphenicol were less common in these locations. Meanwhile, the high resistance of bacteria against the antibiotic in Tanjung Lumpur existed in Polymyxin B, Penicillin G and Ampicillin, whilst no resistance in bacteria were found in Chloramphenicol, Gentamycin and Erythromycin. Overall, the Multiple Antibiotic Resistance (MAR) index value of the isolated bacteria in all location ranged from 0.2 to 1.0. Most of the Gram negative isolates showed MAR index value higher than 0.2 compared to the Gram positive isolates. Approximately, most of the isolates showed MAR index value higher than 0.2 (>0.2) which suggest that there are high-risk of antibiotics contamination in the area. Hence, findings from this preliminary study revealed that there is presence of antibiotic resistance strain of bacteria which may indicate that there is contamination of antibiotics at the coastal water of Pahang, Malaysia and this may pose a potential public health hazard. Keywords—Antibiotic resistance bacteria, sediment, coastal water, Pahang.